A Simple and Efficient Method to Cryopreserve Human Ejaculated and Testicular Spermatozoa in −80°C Freezer - Wang, Xiaohan; Lu, Fangting; Bai, Shun; Wu, Limin; Huang, Lingli; Zhou, Naru; Xu, Bo; Wan, Yangyang; Jin, Rentao; Jiang, Xiaohua; Tong, Xianhong (Frontiers in Genetics, 2022)
Human autologous sperm freezing involves ejaculated sperm, and testicular and epididymal puncture sperm freezing, and autologous sperm freezing is widely used in assisted reproductive technology. In previous studies, researchers have tried to cryopreserve sperm from mammals (rats, dogs, etc.) using a -80 °C freezer and have achieved success. It is common to use liquid nitrogen vapor rapid freezing to cryopreserve human autologous sperm. However, the operation of this cooling method is complicated, and the temperature drop is unstable. In this study, we compared the quality of human ejaculation and testicular sperm after liquid nitrogen vapor rapid freezing and -80 °C freezing for the first time. By analyzing sperm quality parameters of 93 ejaculated sperm and 10 testicular sperm after liquid nitrogen vapor rapid freezing and -80 °C freezing, we found reactive oxygen species (ROS) of sperm of the -80 °C freezer was significantly lower than vapor rapid freezing. Regression analysis showed that progressive motility, ROS, and DNA fragmentation index (DFI) in post-thaw spermatozoa were correlated with sperm progressive motility, ROS, and DFI before freezing. For the freezing method, the -80 °C freezer was positively correlated with the sperm progressive motility. Among the factors of freezing time, long-term freezing was negatively correlated with sperm progressive motility and ROS. Although freezing directly at -80 °C had a slower temperature drop than liquid nitrogen vapor rapid freezing over the same period, the curves of the temperature drop were similar, and slight differences in the freezing point were observed. Furthermore, there were no statistically significant differences between the two methods for freezing testicular sperm. The method of direct -80℃ freezing could be considered a simplified alternative to vapor freezing for short-term human sperm storage. It could be used for cryopreservation of autologous sperm (especially testicular sperm) by in vitro fertilization centers.